Avian proto-myc genes promoted by defective or nondefective retroviruses are single-hit transforming genes in primary cells. - Zhou, R P (1989)
Lymphomas of certain strains of chickens infected by retroviruses frequently contain recombinant transforming genes in which the promoter of the cellular proto-myc gene is replaced by that of a defective rather than an intact retrovirus. Here we ask whether the resulting hybrid genes are sufficient for tumorigenic transformation like viral myc genes. Further, we ask whether retroviruses must be defective in order to mutate proto-myc to a transforming gene or whether the defectiveness plays a transformation-independent function in tumorigenesis. For this purpose the defective provirus of proviral-proto-myc recombinants from lymphomas were repaired, or intact proviruses were recombined with proto-myc genes in vitro, and then compared to recombinant proto-myc genes with defective proviruses for transforming function in quail embryo fibroblasts. It was found that a single copy of a provirus-proto-myc recombinant gene with an intact provirus is sufficient to transform a quail embryo cell in vitro. Moreover, our analyses showed that multiple internal retroviral deletions [corrected] eliminate or inhibit provirus expression. The effect of these deletions [corrected] was detectable only because the inactive proviruses were linked to the selectable, transforming proto-myc gene marker. It is consistent with our results that proviral defectiveness of recombinant proto-myc genes is necessary in vivo for the clonal growth of a transformed cell into a tumor to escape antiviral immunity. The large discrepancy between the probabilities of provirus insertion and tumorigenesis is suggested to reflect the low probabilities of spontaneous deletion of the provirus and of rare, strain-specific defects of tumor-resistance genes of the host.